Health policy analysis of universal coverage implementation in national health systems and services governance financing - Suprapto Suprapto (Lembaga Edukasi Ilmiah Indonesia, 2026)
Introduction: Universal Health Coverage (UHC) is a central objective of national health systems, aiming to ensure equitable access to quality health services without financial hardship. Despite global commitments, countries vary widely in UHC implementation due to differences in governance, financing mechanisms, and system capacity. This study analyzes health policy approaches to UHC implementation with a focus on governance and financing arrangements within national health systems. Methods: A qualitative policy analysis was conducted using a narrative review of peer‑reviewed articles, policy documents, and reports from international health organizations published between 2015 and 2024. Data were analyzed using a health systems framework emphasizing governance, financing, and service delivery dimensions. Cross‑country comparisons were applied to identify common patterns, challenges, and enabling factors in UHC implementation. Results: The analysis shows that strong governance structures, clear regulatory frameworks, and political commitment are critical for effective UHC implementation. Sustainable financing characterized by pooled funding, strategic purchasing, and reduced out‑of‑pocket payments was consistently associated with improved service coverage and financial protection. Fragmented governance and inadequate financing mechanisms remained major barriers, particularly in low‑ and middle‑income countries. Conclusion: Effective UHC implementation requires integrated governance and financing reforms aligned with national contexts. Policy coherence, institutional capacity strengthening, and adaptive financing strategies are essential to improve system performance and equity.